Lipid Remodeling in Hepatocyte Proliferation and Hepatocellular Carcinoma. Issue 3 (3rd November 2020) - Hall, Zoe; Chiarugi, Davide; Charidemou, Evelina; Leslie, Jack; Scott, Emma; Pellegrinet, Luca; Allison, Michael; Mocciaro, Gabriele; Anstee, Quentin M.; Evan, Gerard I.; Hoare, Matthew; Vidal‐Puig, Antonio; et al.
Abstract : Background and Aims: Hepatocytes undergo profound metabolic rewiring when primed to proliferate during compensatory regeneration and in hepatocellular carcinoma (HCC). However, the metabolic control of these processes is not fully understood. In order to capture the metabolic signature of proliferating hepatocytes, we applied state‐of‐the‐art systems biology approaches to models of liver regeneration, pharmacologically and genetically activated cell proliferation, and HCC. Approach and Results: Integrating metabolomics, lipidomics, and transcriptomics, we link changes in the lipidome of proliferating hepatocytes to altered metabolic pathways including lipogenesis, fatty acid desaturation, and generation of phosphatidylcholine (PC). We confirm this altered lipid signature in human HCC and show a positive correlation of monounsaturated PC with hallmarks of cell proliferation and hepatic carcinogenesis. Conclusions: Overall, we demonstrate that specific lipid metabolic pathways are coherently altered when hepatocytes switch to proliferation. These represent a source of targets for the development of therapeutic strategies and prognostic biomarkers of HCC.